TI_GERICHTE 11.2013.85 vom 18. November 2015 , Diritto di compera dei parenti: modalità d'esercizio e prescrizione - TI Tribunale d'appello (2015)
Diritto di compera dei parenti: modalità d'esercizio e prescrizione